Exchange interactions of spin-active metallofullerenes in solid-state carbon networks - Zaka, M; Warner, J; Ito, Y; Morton, J; Rümmeli, M; Pichler, T; Ardavan, A; Shinohara, H; Briggs, G (2010)
The electron paramagnetic resonance (EPR) of spin-active metallofullerenes (MFs) La@ C82 and Sc@ C82 diluted in solid-state C60 crystalline matrices with molar concentrations varying from 0.4% to 100% are investigated. For dilute concentrations, the hyperfine structure of the MFs is resolved, and as the concentration increases exchange narrowing is observed leading to a single peak in the EPR. Sc@ C82 MFs are inserted into single-walled carbon nanotubes to form peapods with concentrations of 10% and 0.1%, diluted with C60. For the case of peapods containing 10% Sc@ C82 a strong narrow peak is observed in X -band CW EPR, but not pulsed measurements. Peapods containing Ce@ C82 MFs are prepared and these also show similar CW EPR to the Sc@ C82, indicating the peak arises from charge transfer with the SWNT. © 2010 The American Physical Society.